2021
DOI: 10.3390/ijerph18084058
|View full text |Cite
|
Sign up to set email alerts
|

Thallium Contamination of Drinking Water: Health Implications in a Residential Cohort Study in Tuscany (Italy)

Abstract: In 2014–2015, concentrations of thallium above the recommended reference value (EPA: 2 µg/L) were measured in some parts of the drinking water distribution system in the municipality of Pietrasanta (Tuscany, Italy). An extensive campaign of water samples and human biomonitoring surveys were implemented to quantify the exposure of population. A residential cohort epidemiological study was carried out on the population of the municipality of Pietrasanta, aimed at comparing the health status of residents in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Examples of criteria can be found in references [6,7]. In the United States, the maximum Tl level in drinking water and wastewater discharge has been set at 2 and 140 µg/L, respectively, by the USEPA [6,[16][17][18][19]. In China, the Tl concentration limit has been lowered to 0.1 µg/L and 2 µg/L for drinking water and industrial wastewater, respectively, in some provinces [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of criteria can be found in references [6,7]. In the United States, the maximum Tl level in drinking water and wastewater discharge has been set at 2 and 140 µg/L, respectively, by the USEPA [6,[16][17][18][19]. In China, the Tl concentration limit has been lowered to 0.1 µg/L and 2 µg/L for drinking water and industrial wastewater, respectively, in some provinces [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…To date, few studies have reported adsorption behavior and removal efficiency of thallium (I) at low concentration. As a matter of fact, most of the investigations were carried out at high thallium (I) concentration ranging from 1-150 mg.L −1 , whereas thallium is found to be in the range of a few µg.L −1 in real polluted water sources [11,16,28]. In this paper, the removal of Tl(I) ions at low concentration, through adsorption onto synthesized gamma-alumina nanoparticles, was investigated for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…If the Cl contamination is accompanied by contaminants such as thallium, this could be of concern. Notably, the ingestion of thallium above the USEPA MCL in drinking water has previously been associated with increased risk of low birth weights, 64 and low birth weights have been documented in populations in SWPA exposed to a high density of UOGD. 43 These results point toward potential human exposure risk via water supplies contaminated by UOGD in limited areas.…”
Section: Regional-scale Impacts Of Uogd On [Ch 4 ] and [Cl]mentioning
confidence: 99%
“…However, different studies dealing with human health effects after Tl chronic ingestion provide contradictory results. For instance, Nuvolone et al (2021) studied the effect of high Tl concentrations (above EPA recommended reference values) in the drinking water distribution of Tuscany (Italy) and they did not report any excess of risk in terms of mortality and hospitalization in the population exposed to Tl compared to those non-exposed from other not contaminated areas. On the other hand, Campanella et al (2019) reviewed the toxicity of Tl at low doses and highlight that Tl exposure, even at very low concentrations, represents a threat to human health, recommending to revise the concentration limits of Tl in the various environmental compartments.…”
Section: Dissolved and Particulate Concentrationsmentioning
confidence: 99%